Linchamento : representações sociais, motivações para linchar, simpatia ideológica, atitude institucional e fatores preditores - Alexandre, Maria Edna Silva de (2018)
The lynching phenomenon has been recurrent in Brazil, as well as in the international scenario, challenging the institutions officially responsible for the justice application, from the dissemination of extra-legal cases. This is a peculiar form of collective violence, in which a group of people gather to attack and even kill one or more of those accused of breaking a social norm. Despite the social coexistence implications related to the naturalization and legitimation of the lynching practice, investigations on this phenomenon are still incipient in the national and international context, in all knowledge areas, especially related to Psychology. Considering these limitations, this dissertation sought to broaden the lynching understanding, the motivations to lynch and the predictive factors to its favorability. To do this, two empirical studies were carried out. The first one aimed to identify the social representations of university students on lynching and the motivations to lynch. It is a field study, quantitative and qualitative, descriptive and exploratory, with a non-probabilistic sample with the intentional type. In this, 122 students of Psychology and Exact Sciences participated, who answered a list of sociodemographic data and two semi-structured questionnaires on lynching and its motivations. The analyzes, through the Descending Hierarchical Classifications, allowed us to identify that the constructs are represented by the groups researched from the societal and socio-emotional notions appropriations that make the lynching phenomenon intelligible, as well as evidence anchorages in sociodemographic variables (religion, age, course and period of the participants). The second study aimed to verify the predictive power of ideological sympathy and institutional attitude regarding favorability to the lynching. It is a quantitative search, with a descriptive, exploratory and correlational nature. It was attended by 850 Brazilians, who answered a sociodemographic questionnaire, two Scales of Attitudes toward Lynching - one with a moral dilemma and another without it, the Ideological Sympathy Scale and the Institutional Attitude Scale. The results indicated differences according to the sociodemographic variables in relation to the lynching favorability; as well as, evidenced that ideological sympathy contributed more than the institutional attitude to predict lynching favorability, resulting in a model that predicts a significant portion of the phenomenon. Broadly, the results of the two empirical studies showed that lynching contains a problem rooted in psycho-sociological dimensions. These are significant and innovative contributions to the lynching understanding, in addition to legitimizing the place of Social Psychology in this process.